Phytotoxicity of the herbicide CP 50144 FOR (Sesamum indicum L.) and Phaseolus vulgaris L. cultivated in nutrient solutions - Camargo, Paulo Nogueira de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
This paper describes an experiment on the phytotoxicity of the herbicide 2-Chloro-2',6'-diethyl-N-(methoxymethyl) acetanilide (CP 50144) on seedlings of sesame (Sesamum indicum) and bean (Phaseolus Vulgaris L.) cultivated in nutrient solutions. Foliar treatments were made by applying respectively concentrations of 1mg/10l, 5mg/10l, 25mg/10l, 125mg/10l, 250mg/ 10l and 500mg/10l of the herbicide, through a lOlmicropipettes, in the base of the primary leaves. Root treatments were made by applying the herbicide, in the concentrations of 1 ppm, 5ppm, 25 ppm, 125 ppm 625 ppm and 3125 ppm, into the nutrient solu -tion (0,5 Hoagland). Foliar absorption of CP 50144 by the leaves is relatively slow, but when the herbicide passes thru the cuticle,its contact action is intense, showing little acropetal translocation. In foliar applications, sesame showed high tolerance to the concentrations from 1 to 125mg/10l , being not injured at all. Higher concentrations revealed themselves very phytotoxic, injurying severely the leaves. The bean seedlings leaves were injured by all concentrations of CP 50144, except for the one at lmg/10l. In root applications, sesame showed also, high tolerance to the herbicide, being not injured at all by the concentrations from 1 to 125 ppm. Higher concentrations produced severe contact injuries in the roots and general symptoms of phytotoxicity on the foliage. The plants dead. This seems to be due to the fact that these concentrations were stronger than the saturation point of the herbicide in water (148 ppm). The water insoluble herbicides (dissolved in the solvent vehicle) may be produced the contact injuries in the root system, and may be absorbed and translocated in the transpiration stream, affecting severely all the plant. The bean plants showed high sensibility to the herbicide, in root treatments. All the plants were killed in all concentrations. The symptoms were described. It seems that the herbicide affects the cellular distension of the young leaves, as these ones showed themselves coriaceous, corrugated and concavous. There are needs of further studies on the mode of action of CP 50144 to explain its phytotoxic effects and selectivity for sesame and other tolerant plants. The author thanks Prof. David J. Rincón for his advice, and Mrs. Mary P. de Veras and Don Juan Ramirez for their very capable assistance.